Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, dan Motivasi terhadap Kinerja Karyawan di PT Tiki Jalur Nugraha Ekakurir (JNE) Cabang Surabaya - Rahmawanto, Indra; Arifin, Syamsul; Siswohadi Siswohadi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of leadership style, work environment and motivation on employee performance at PT Tiki Jalur Nugraha Ekakurir (JNE) Surabaya Branch. The data were collected through observation and questionnaires, and analyzed by using linear regression, t test and f test. The results show that: (1) There is a positive and significant influence of leadership style on employee performance, as indicated by the t-value (2.301) > t-table (2.0086), meaning that leadership style contributes to improving employee performance. (2) The work environment also has a significant effect on employee performance, with a t-value (2.397) > t-table (2.0086). (3) Motivation significantly affects employee performance, shown by a t-value (2.128) > t-table (2.0086). (4) Simultaneously, leadership style, work environment, and motivation have a significant impact on employee performance, as shown by the F-test significance value of 0.000 < 0.05 and an F-value (17.624) > F-table (2.79). These findings indicate that all three independent variables together have a significant influence on employee performance at PT. Tiki Jalur Nugraha Ekakurir (JNE) Surabaya Branch.